EVALUATING THE USE OF VIRTUAL SURGICAL PLANNING IN OPTIMIZING OUTCOME IN THE TREATMENT OF TMJ ANKYLOSIS (Journal of Medical & Health Sciences Review, 2025)
Background: A terrible illness that impairs jaw function and quality of life is temporomandibular joint (TMJ) ankylosis. Virtual surgical planning (VSP), a useful tool for improving surgical results, has become one among several available options. The current research assesses VSP's application in TMJ ankylosis therapy. Objective:To investigate the effectiveness of virtual surgical planning in optimizing outcomes in the treatment of TMJ ankylosis.Methods: This study used retrospective cohort methodology. Data were gathered from 30 TMJ ankylosis patients (ages 15–45 years) in the Maxillofacial surgery unit of tertiary care hospitals' Data on surgical planning, implementation, and results were gathered using a standardized questionnaire. Statistical analysis was performed using paired t-test and Wilcoxon signed-rank test on Patient's demographics, medical history, and surgical outcomes retrieved from patient’s record.Results: Significant improvement was found in Mouth Opening: Mean rise of 12 mm (p < 0.001). Joint Function: Reduced pain (P